2018
DOI: 10.1002/ange.201809165
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation and Manipulation of Supramolecular Polymerization by High‐Speed Atomic Force Microscopy

Abstract: Despite recent advances in mechanistic understanding and controlled-synthesis methodologies regardingsynthetic supramolecular assemblies,i th as remained challenging to capture the molecular-level phenomena in real time,t hus hindering further progress in this researchf ield. In this study, we applied high-speed atomic-force microscopy(AFM), which has extraordinary spatiotemporal resolution (1 nm and sub-100 ms), to capture dynamic events occurring during synthetic molecular self-assembly.H igh-speed AFM permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
7
0
3
Order By: Relevance
“…219 Seeded growth approaches were studied in detail for systems based on zinc porphyrins amphiphiles in 2014 with impressive length control of the resulting low dispersity fibers evidenced for the first time (see Figure 5b). 220,223,224 Kinetic studies revealed 1 st order growth behavior with respect to the zinc porphyrin amphiphile which is analogous to that expected for a conventional living chain-growth covalent polymerization.…”
Section: Chemical Science Accepted Manuscriptsupporting
confidence: 58%
“…219 Seeded growth approaches were studied in detail for systems based on zinc porphyrins amphiphiles in 2014 with impressive length control of the resulting low dispersity fibers evidenced for the first time (see Figure 5b). 220,223,224 Kinetic studies revealed 1 st order growth behavior with respect to the zinc porphyrin amphiphile which is analogous to that expected for a conventional living chain-growth covalent polymerization.…”
Section: Chemical Science Accepted Manuscriptsupporting
confidence: 58%
“…However, with the exception of modern environmental TEM, this technique demands that the sample holder be confined to a small volume and held at ultrahigh vacuum (UHV) (Figure ). We note that there are other potential imaging techniques outside of the scope of this review, each with its own set of opportunities and artefacts, including atomic force microscopy, ion microscopy, and synchrotron X-ray microscopy. …”
Section: Introductionmentioning
confidence: 99%
“…Die photostationären Zustände hängen dabei vornehmlich von den verwendeten Liganden und Lçsungsmitteln ab. Basierend auf der Versatilitätv on Metallkomplexen in der Ausbildung direktionaler Wechselwirkungen, würde diese Strategie das vorhandene Arsenal zur Erzeugung stimuliresponsiver Materialien [7] und lebender supramolekularer Polimerisation [8] erweitern. [6] Um die vorhandene Reichweite von Koordinationsisomerie zu erweitern, kçnnte die inhärent unterschiedliche Geometrie von cis-und trans-Pt II -Komplexen als neue Methode zur Kontrolle von Selbstassemblierungsprozessen dienen.…”
unclassified
“…[6] Um die vorhandene Reichweite von Koordinationsisomerie zu erweitern, kçnnte die inhärent unterschiedliche Geometrie von cis-und trans-Pt II -Komplexen als neue Methode zur Kontrolle von Selbstassemblierungsprozessen dienen. Basierend auf der Versatilitätv on Metallkomplexen in der Ausbildung direktionaler Wechselwirkungen, würde diese Strategie das vorhandene Arsenal zur Erzeugung stimuliresponsiver Materialien [7] und lebender supramolekularer Polimerisation [8] erweitern.Die Existenz von kleinen und/oder sterisch nicht eingeschränkten Liganden scheint fürd as Vorkommen von geometrischer Isomerie in Pt II -Komplexen Voraussetzung zu sein. [9,10] Andernfalls führen sterische Abstoßung zwischen cis-koordinierten Liganden sowie die stärkere Tendenz zur Aggregation der präorganisierten trans-Spezies zur Stabilisierung der trans-Form.…”
unclassified
See 1 more Smart Citation